2013
DOI: 10.1007/s10545-013-9668-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect of coenzyme Q10 and an antioxidant cocktail in fibroblasts of patients with Sanfilippo disease

Abstract: Coenzyme Q10 (CoQ10) plays a key role in the exchange of electrons in lysosomal membrane, which contributes to protons' translocation into the lumen and to the acidification of intra-lysosomal medium, which is essential for the proteolytic function of hydrolases responsible -when deficient- of a wide range of inherited lysosomal diseases such as Sanfilippo syndromes. Our aim was to evaluate whether treatment with CoQ10 or with an antioxidant cocktail (α-tocopherol, N-acetylcysteine and α-lipoic acid) were able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Total cholesterol values were normal, suggesting that the cause of such deficiency is probably unrelated to impaired cholesterol biosynthesis (and consequently CoQ biosynthesis). This statement would be supported by the data of Matalonga et al, who demonstrated a normal CoQ biosynthesis rate in cultured skin fibroblast from MPS patients (Matalonga et al 2014). Plasma CoQ values depend on dietary sources (around 20% of total CoQ) and liver biosynthesis, but dietary CoQ deficiency is unlikely considering the adequate nutritional status of our patients and the normality of most of the other vitamins and trace elements analyzed.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Total cholesterol values were normal, suggesting that the cause of such deficiency is probably unrelated to impaired cholesterol biosynthesis (and consequently CoQ biosynthesis). This statement would be supported by the data of Matalonga et al, who demonstrated a normal CoQ biosynthesis rate in cultured skin fibroblast from MPS patients (Matalonga et al 2014). Plasma CoQ values depend on dietary sources (around 20% of total CoQ) and liver biosynthesis, but dietary CoQ deficiency is unlikely considering the adequate nutritional status of our patients and the normality of most of the other vitamins and trace elements analyzed.…”
Section: Discussionsupporting
confidence: 80%
“…Increased CoQ consumption may also be a factor explaining this deficiency, since some authors suggested the possible involvement of the reactive oxygen species in the MPS type IIIB disease pathogenesis (Villani et al 2009). Recently a positive effect has been observed in cultured fibroblasts from Sanfilippo A and B treated with CoQ and other antioxidants (Matalonga et al 2014). Moreover, since CoQ participates in tocopherol recycling (Navas et al 2007), the significantly lower median tocopherol values observed in our MPS patients when compared with age-matched controls might be related with the CoQ deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in lipid/sterol metabolism as a result of GCase inhibition may impact on the biosynthesis of CoQ 10 ( Hargreaves, 2014 ). Alternatively, CoQ10 is also known to play a role in the proton translocation across the lysosomal membrane ( Matalonga et al, 2014 ), and the lysosomal accumulation of substrate in GD may have an effect on the lysosomal pool of CoQ 10 . Despite the uncertainty, it is becoming increasingly clear that treatment with CoQ 10 or analogues such as MitoQ can partially reverse the mitochondrial dysfunction and oxidative stress observed in cell models of GD and other lysosomal storage disorders ( De la Mata et al, 2015 , Matalonga et al, 2014 , Osellame et al, 2013 ).…”
Section: Glucocerebrosidasementioning
confidence: 99%
“…Likewise, as mitochondrial dysfunction and/or impaired mitochondria elimination may be associated to alterations of lysosome-dependent processes, coenzyme Q 10 (CoQ), an antioxidant and mitochondrial energizer, is currently considered as a potential experimental drug for the treatment of neurodegenerative diseases in general 24 and lysosomal diseases in particular 25 . We conceived that addressing both mutant GCase rescuing by NAdBT-AIJ as PC and mitochondrial function by CoQ might lead to beneficial synergies.…”
mentioning
confidence: 99%